A Safe Surgical Hip Dislocation For Treating Pipkin Fracture: a case report - Jayanegara, R.Muhammad David (The Hip and Knee Journal, 2024)
Pipkin fractures are rare events and usually occur as a consequence for high-energy trauma. Surgery to obtain anatomical reduction and fixation is the mainstay treatment for the majority of these injuries. The surgical treatment for Pipkin fractures remains a source of controversy, especially regarding the best surgical approach. Case presentation a 18-year-old male, which sustained a type I Pipkin fracture following a motorcycle accident. In the emergency department, an emergent closed reduction was performed, followed by surgery two weeks later. Using a surgical hip dislocation, a successful anatomical reduction and fixation was performed. The discussion safe surgical hip dislocation allows full access to the femoral head and acetabulum, without increasing the risk for a femoral head avascular necrosis or posttraumatic arthritis and minimizing trauma to the abductor musculature. Simultaneously, this surgical approach gives the opportunity to repair associated acetabular or labral lesions, which explains the growing popularity with this technique. The conclusion although technically demanding, safe surgical hip dislocation represents an excellent option in the reduction and fixation for Pipkin fractures.